Which of the following correctly demonstrates the Associative Property of Addition?(1 point)

A-m*(x*y)=(m*x)*y

B-x*(y+z)=(x*y)+z

C-y-(x+1)=(y+x)+1

D-(x+y)+z+r=x+(y+z)+r

1 answer

The correct option that demonstrates the Associative Property of Addition is:

D - \(-(x+y)+z+r=x+(y+z)+r\)

The Associative Property of Addition states that the way in which numbers are grouped when adding does not change their sum. In option D, you can see the grouping of additions being rearranged while keeping the same sum.